2021
DOI: 10.1038/s41598-021-85510-0
|View full text |Cite
|
Sign up to set email alerts
|

The TOMM40 ‘523’ polymorphism in disease risk and age of symptom onset in two independent cohorts of Parkinson’s disease

Megan C. Bakeberg,
Madison E. Hoes,
Anastazja M. Gorecki
et al.

Abstract: Abnormal mitochondrial function is a key process in the pathogenesis of Parkinson’s disease (PD). The central pore-forming protein TOM40 of the mitochondria is encoded by the translocase of outer mitochondrial membrane 40 homologue gene (TOMM40). The highly variant ‘523’ poly-T repeat is associated with age-related cognitive decline and age of onset in Alzheimer’s disease, but whether it plays a role in modifying the risk or clinical course of PD it yet to be elucidated. The TOMM40 ‘523’ allele length was dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Within studies examining cognitive decline in nonpathological ageing populations [19][20][21][22] and in cohorts of individuals with AD 17,18 , the mitochondrial variant TOMM40 '523' has been implicated with mixed results. By comparison, two studies have found no association between the TOMM40 '523' and PD risk 32,33 , while a third group found that the L/VL '523' genotype was overrepresented in Swedish PD patients when compared to controls 31 . However, research into whether TOMM40 '523' alleles play a role in modulating cognitive impairment and rate of decline within PD is profoundly scant, with only a single cross-sectional study of a In past literature, case-control analysis has found that while TOMM40 '523' does not modulate or influence the risk of developing PD, it may affect the age at which symptoms develop 32,33 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Within studies examining cognitive decline in nonpathological ageing populations [19][20][21][22] and in cohorts of individuals with AD 17,18 , the mitochondrial variant TOMM40 '523' has been implicated with mixed results. By comparison, two studies have found no association between the TOMM40 '523' and PD risk 32,33 , while a third group found that the L/VL '523' genotype was overrepresented in Swedish PD patients when compared to controls 31 . However, research into whether TOMM40 '523' alleles play a role in modulating cognitive impairment and rate of decline within PD is profoundly scant, with only a single cross-sectional study of a In past literature, case-control analysis has found that while TOMM40 '523' does not modulate or influence the risk of developing PD, it may affect the age at which symptoms develop 32,33 .…”
Section: Discussionmentioning
confidence: 91%
“…By comparison, two studies have found no association between the TOMM40 '523' and PD risk 32,33 , while a third group found that the L/VL '523' genotype was overrepresented in Swedish PD patients when compared to controls 31 . However, research into whether TOMM40 '523' alleles play a role in modulating cognitive impairment and rate of decline within PD is profoundly scant, with only a single cross-sectional study of a In past literature, case-control analysis has found that while TOMM40 '523' does not modulate or influence the risk of developing PD, it may affect the age at which symptoms develop 32,33 . The findings of the present study provide evidence that polymorphism in TOMM40 '523' may also have significant effects on cognitive decline and progression to PDD, independent of the influence of APOE ε4.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Importantly, changes in the size and composition of both SV/SSVs can have a significant impact on the binding of regulatory elements that modulate RNA processing and gene expression [16]. SSVs have been implicated in many complex diseases, including ALS and other neurodegenerative diseases [17], such as Parkinson's and Alzheimer's disease [18][19][20]. The ability of SSVs to alter gene expression is dependent on their location within and around the gene or intergenic region, with their effects occurring via several mechanisms including the following: influencing the binding of regulatory elements, mRNA splicing and processing, genome folding and higher order structure, and translation.…”
Section: Introductionmentioning
confidence: 99%